Styles of Intergenerational Pedagogical Interaction of Teachers and Students of Different Generational Groups - Vlada I. Pishchik; Anna V. Gavrilova; Nadezhda V. Sivrikova (Rossijskij psihologičeskij žurnal., 2016)
The paper brings forward the results of an empirical study of styles of intergenerational pedagogical interaction of teachers (representatives of the Soviet and transitional generations), and students (representatives of the post-Soviet generation). The authors overviewed the existing research on the issue of intergenerational interaction. The purpose of the study was to establish the dominant styles of intergenerational pedagogical interaction and their socio-psychological components in teachers and students of the institutes of higher education. A. A. Bodalev’s ideas about communication and V. I. Pishchik’s concept of the mentality of generations formed theoretical foundations for the present work. The study involved teachers of two generational groups (the Soviet and transitional generations), and students (the post-Soviet generation); each group of the sample consisted of 60 persons. Applying the techniques the authors studied the following generational factors: identification with the generation (Soviet, transitional, post-Soviet); type of mentality of the generation (traditional, transitional, innovative, postinnovative); socio-sychological characteristics of interaction (interpersonal relations, communicative attitude, personal characteristics, and interaction style). The empirical study revealed that indifferent and conforming styles of intergenerational pedagogical communication were characteristic to teachers of the Soviet generation; manipulative and indifferent styles of intergenerational pedagogical communication were characteristic to teachers of the transitional generation; apathetic; manipulative and indifferent styles of intergenerational pedagogical communication were characteristic to students of the post-Soviet generation. Cluster analysis revealed the components of the preferred style of interaction. The study established interconnected clusters, which included the preferred styles of interaction and socio-psychological characteristics of interaction: interpersonal relations, communicative attitudes, personal characteristics. This paper has clearly shown that teachers and students prefer to use different styles of intergenerational pedagogical interaction, which depends on their generational identification. The components of the same style of intergenerational pedagogical interaction differ in students and teachers of different generational groups. Innovative mentality is characteristic for the teachers of the transitional generation and the students of the post-Soviet generation; manipulative style is the leading style of intergenerational pedagogical interaction, which confirms the hypothesis that the convergence and similarity of the mentality of teachers and students of different generations determines the choice of the style of pedagogical interaction.